Nomogram predicting the risk of recurrence after curative‐intent resection of primary non‐metastatic gastrointestinal neuroendocrine tumors: An analysis of the U.S. Neuroendocrine Tumor Study Group. Issue 5 (15th February 2018) - Merath, Katiuscha; Bagante, Fabio; Beal, Eliza W.; Lopez‐Aguiar, Alexandra G.; Poultsides, George; Makris, Eleftherios; Rocha, Flavio; Kanji, Zaheer; Weber, Sharon; Fisher, Alexander; Fields, Ryan; Krasnick, Bradley A.; et al.
Abstract : Background: The risk of recurrence after resection of non‐metastatic gastro‐entero‐pancreatic neuroendocrine tumors (GEP‐NET) is poorly defined. We developed/validated a nomogram to predict risk of recurrence after curative‐intent resection. Methods: A training set to develop the nomogram and test set for validation were identified. The predictive ability of the nomogram was assessed using c‐indices. Results: Among 1477 patients, 673 (46%) were included in the training set and 804 (54%) in y the test set. On multivariable analysis, Ki‐67, tumor size, nodal status, and invasion of adjacent organs were independent predictors of DFS. The risk of death increased by 8% for each percentage increase in the Ki‐67 index (HR 1.08, 95% CI, 1.05‐1.10; P < 0.001). GEP‐NET invading adjacent organs had a HR of 1.65 (95% CI, 1.03‐2.65; P = 0.038), similar to tumors ≥3 cm (HR 1.67, 95% CI, 1.11‐2.51; P = 0.014). Patients with 1‐3 positive nodes and patients with >3 positive nodes had a HR of 1.81 (95% CI, 1.12‐2.87; P = 0.014) and 2.51 (95% CI, 1.50‐4.24; P < 0.001), respectively. The nomogram demonstrated good ability to predict risk of recurrence (c‐index: training set, 0.739; test set, 0.718). Conclusion: The nomogram was able to predict the risk of recurrence and can be easily applied in the clinical setting.